O02 CLEVER: clinical evaluation of WEB 0.017 device in Intracranial AneuRysms Safety results for ruptured and unruptured aneurysm at 30 days. (29th August 2022) - Szikora, I; Cognard, C; Costalat, V; Wodarg, F; Herbreteau, D; Fischer, S; Möhlenbruch, M; Papagiannaki, C; Klisch, J; Rautio, R; Numminen, J; Berlis, A; et al.
Abstract : Introduction: Intrasaccular flow disruption is an endovascular approach for treatment of wide-neck bifurcation aneurysms. Earlier models of The WEB device have demonstrated their efficacy and safety. Aim: CLEVER objective is to provide safety and efficacy data on the WEB 0.017 model in treatment of ruptured and unruptured bifurcation aneurysms. We report description of the full population and safety results within 30 days post procedure. Methods: CLEVER is a prospective, multicenter study conducted in 17 European sites. Data collected are 100% monitored and primary endpoints independently evaluated (occlusion rates assessed by a Corelab and adverse events adjudicated by CEC). Analysis was performed for the full population and separately for rutupred/unruptured aneurysm. ITT analysis is performed for safety population, and sample size calculation is based on OPC approach for safety and efficacy rates. Results: 163 patients with 103 unruptured aneurysms and 60 ruptured aneurysms were enrolled. Aneurysms locations were mainlyACom (37.4%), and MCA bifurcation (30.1%) location. Aneurysms treated were ranging from 2 to 9.2mm (mean maximum sac width = 5.0mm). The WEB procedure was successfully completed in the 163 patients. For this report covering analysis of data up to 30 days post procedure: major strokes rate was 1.2% and mortality rate was 0%. A detailed description of events reported up to 30 days will be provided. Conclusion: These results show good safety profile at 1 month, withlow rate of neurological/neurovascular event with permanent deficit and no mortality at 30 days, confirming the safety of WEB0.017use in intracranial aneurysm treatment, unruptured or ruptured. References: Pierot et al . Aneurysm Treatment with Web in the Cumulative Population of Two Prospective, Multicenter Series: 3-year Follow-up. J Neurointerv Surg, 2020 Do you have any conflict of interest to declare? : Yes Conflict of Interest Statement: Steering Committee member of the CLEVER study Consulting agreements with Microvention, Medtronic, Stryker, Cerenovus